Optimising the Supervision of the Use of Village Funds through the Digital-Based Village Guard Program at the Bantaeng District Attorney's Office - Nur Nisa; Herman H; A Thirta Massaguni D; Fauziyah Fauziyah (Program Pascasarjana Universitas Negeri Makassar, 2023)
Along with the development of village governance management and in an effort to realise excellent and quality services, as well as the great authority given to the village to plan development and manage its own budget, it is intended to empower and improve the welfare of the village community. This authority also provides opportunities for all village communities to participate in village planning and development. Integrated supervision between the prosecutor's office and the village government will bring various benefits. In addition, integrated supervision will also encourage transparency and community participation in the use of village funds. With a more effective supervision system in place, the community will feel more confident and involved in overseeing the use of village funds, thereby preventing and uncovering potential abuses. It is therefore important that we encourage and support the idea of a change in the supervision of the use of village funds that is integrated between the prosecutor's office and the village government. This can ensure transparent, accountable use of village funds, providing real benefits for the development and welfare of village communities. Then the Village Guard Information System (SI-JAGAD) was developed at the Bantaeng District Attorney's Office to optimise supervision of the use of the Village Fund. The data collection technique was carried out using a questionnaire instrument with closed and open question models. Respondents were asked to provide answers according to the conditions experienced. To determine the reliability coefficient of the questionnaire, Cronbach's Alpha was used.